Geopolymer Ceramic Application: A Review on Mix Design, Properties and Reinforcement Enhancement - Nurul Aida, Mohd Mortar; Mohd Mustafa Al Bakri, Abdullah; Rafiza, Abd Razak; Shayfull Zamree, Abd Rahim; Ikmal Hakem, Aziz; Nabiałek, Marcin; Putra Jaya, Ramadhansyah; Semenescu, Augustin; Rosnita, Mohamed; Mohd Fathullah, . (MDPI AG, Basel, Switzerland, 2022)
Geopolymers have been intensively explored over the past several decades and consid‐ ered as green materials and may be synthesised from natural sources and wastes. Global attention has been generated by the use of kaolin and calcined kaolin in the production of ceramics, green cement, and concrete for the construction industry and composite materials. The previous findings on ceramic geopolymer mix design and factors affecting their suitability as green ceramics are re‐ viewed. It has been found that kaolin offers significant benefit for ceramic geopolymer applications, including excellent chemical resistance, good mechanical properties, and good thermal properties that allow it to sinter at a low temperature, 200 °C. The review showed that ceramic geopolymers can be made from kaolin with a low calcination temperature that have similar properties to those made from high calcined temperature. However, the choice of alkali activator and chemical com‐ position should be carefully investigated, especially under normal curing conditions, 27 °C. A com‐ prehensive review of the properties of kaolin ceramic geopolymers is also presented, including compressive strength, chemical composition, morphological, and phase analysis. This review also highlights recent findings on the range of sintering temperature in the ceramic geopolymer field which should be performed between 600 °C and 1200 °C. A brief understanding of kaolin geopolymers with a few types of reinforcement towards property enhancement were covered. To improve toughness, the role of zirconia was highlighted. The addition of zirconia between 10% and 40% in geopolymer materials promises better properties and the mechanism reaction is presented. Findings from the review should be used to identify potential strategies that could develop the performance of the kaolin ceramic geopolymers industry in the electronics industry, cement, and biomedical materials.